Embolization of intracranial aneurysms with Guglielmi detachable coils augmented by microballoons. - Sanders, W P; Burke, T H; Mehta, B A (American Journal of Neuroradiology, 1998)
We describe two cases in which balloons were used to aid in the occlusion of intracranial aneurysms with Guglielmi detachable coils. In both patients, initial attempts to place coils within the aneurysmal sac failed, as the loops of the coil repeatedly protruded through a wide aneurysmal neck into the parent vessel. Temporary balloons placed across the neck of these small, wide-necked aneurysms, the bridging balloon technique, effectively narrowed the necks, providing support for the formation of a proper coil basket, which was not possible without the balloon. Follow-up studies at 1 year showed good results in both patients.